Trace element in seagrasses from Merambong shoal, Johore - Ng, Zeit Liang (2013)
Studies on trace element concentrations in seagrass in the temperate area have been carried out extensive over the world. However, trace element concentrations in seagrass from tropical area are of little information. Trace elements in seagrass (As, B, Cd, Cr, Fe, Hg, Ni, Pb and S), sediment (As, B, Cd, Cu, Cr, Na, Hg, Ni, Pb and S) and pore water (As, B, Cd, Cr, Na, Hg, Ni, Pb and S) were determined. Eight seagrass species; Enhalus acoroides, Thalassia hemprichii, Halophila ovalis big-leaved, Halophila ovalis small-leaved, Halophila spinulosa, Cymodocea serrulata, Halodule uninervis narrow-leaved and Halodule uninervis wide-leaved were collected at Merambong shoal, Johore during low tide for 5 months period from April to August. Fresh samples were dried and grind. Dried seagrass and soil sediment were subjected to wet digestion method while pore water were acidified to pH<2 prior to analysis using Perkin Elmer Optima 8300 ICP-OES. Sulfur concentrations were the highest for seagrasses ranged from 5920.30-9507.30 ppm followed by iron concentration (1242.60-7819.00 ppm) while the lowest was arsenic concentration ranged from 0.17-2.67 ppm. Mercury element was not detected in all seagrass species. Soil sediments were the highest concentration for sodium with 2950.20-8270.00 ppm while concentration of arsenic was the lowest (0.13-1.07 ppm). Mercury and boron elements were not detected in soil sediments. In pore water, concentration of sulfur was the highest (598.730-873.610 ppm) followed by boron (2.221-3.489 ppm). The concentrations of the compared trace element were relatively lower than the other studies.